Molecular signaling in multiple myeloma: association of RAS/RAF mutations and MEK/ERK pathway activation - Xu, Jing; Pfarr, Nicole; Endris, Volker; Mai, Elias K.; Hanafiah, Nur Hafzan Md; Giesen, Nicola; Penzel, Roland; Weichert, Wilko; Ho, Anthony Dick; Schirmacher, Peter; Goldschmidt, Hartmut; Andrulis, Mindaugas; et al. (Oncogenesis, 2017)
Multiple myeloma (MM) is a plasma cell malignancy that is still considered to be incurable in most cases. A dominant mutation cluster has been identified in RAS/RAF genes, emphasizing the potential significance of RAS/RAF/MEK/ERK signaling as a therapeutic target. As yet, however, the clinical relevance of this finding is unclear as clinical responses to MEK inhibition in RAS-mutant MM have been mixed. We therefore assessed RAS/RAF mutation status and MEK/ERK pathway activation by both targeted sequencing and phospho-ERK immunohistochemistry in 180 tissue biopsies from 103 patients with newly diagnosed MM (NDMM) and 77 patients with relapsed/refractory MM (rrMM). We found a significant enrichment of RAS/BRAF mutations in rrMM compared to NDMM (P=0.011), which was mainly due to an increase of NRAS mutations (P=0.010). As expected, BRAF mutations were significantly associated with activated downstream signaling. However, only KRAS and not NRAS mutations were associated with pathway activation compared to RAS/BRAFwt (P=0.030). More specifically, only KRASG12D and BRAFV600E were consistently associated with ERK activation (P<0.001 and P=0.006, respectively). Taken together, these results suggest the need for a more specific stratification strategy consisting of both confirmation of protein-level pathway activation as well as detailed RAS/RAF mutation status to allow for a more precise and more effective application of targeted therapies, for example, with BRAF/MEK inhibitors in MM.